Teachers' Written Feedback Technique on Students' Writing Tasks at Prof Dr Hamka Islamic Boarding School Padang Pariaman Regency of West Sumatera - Niza Syaveny; Nora Novisa (JAMBI-ENGLISH LANGUAGE TEACHING, 2017)
Feedback is the information which is given by the teachers to the students’ tasks. The information includes students’ error or mistakes on the tasks. There are some kinds of written feedback on students’ writing tasks, namely; direct, indirect, and coded writing tasks. Those clear to point out students what should do on their tasks. This research was a qualitative research focuses on teachers’ writing feedback techniques on students’ writing tasks. This research was done at Prof. Dr.Hamka Islamic Boarding School of Padang Pariaman regency of West Sumatera. The participants of the research were English teachers on the location of the research. The instruments of the research were observation checklist and students’ writing tasks documentation. The data was analyzed through organizing and familiarizing, coding and reducing, and interpreting and representing (Ary, 2010). Based on the research finding, it was found that two English teachers used direct writing feedback with giving correct words, forms, and answer technique on students writing tasks and indirect writing feedback with indicating the error, self-edited, self-revised, and giving comment technique in correcting students’ writing tasks, while the other English teacher used direct, indirect and coded writing feedback on students’ writing tasks. In conclusion, direct, indirect, and coded feedbacks were used by the English teacher at Prof. Dr. Hamka Islamic Boarding School in giving the information and correcting students’ writing tasks.